Sensory effects of COVID-19 in wine professionals - Theodore J. Witek, Jr.; Natasha Yasmin Sheikhan; Allan Tran (PLoS ONE, 2025)
Objective To evaluate the sensory impacts of COVID-19 infection among wine professionals, and consequences on personal and professional well-being. Our goal was to better understand these effects on an occupational cohort who relies heavily on intact sensory function. Design The study employs an explanatory sequential mixed methods design comprising of two distinct phases: 1) a cross-sectional survey, followed by 2) qualitative interviews with a subsample of survey respondents. Setting Wine professionals were recruited at the global level, excluding locations where Instagram is restricted or banned. Participants Wine professionals (n=128) (ages ≥ 19 years) infected with COVID-19 and experienced sensory impacts were included in the study analysis. Eleven participants completed qualitative interviews. Interventions None. Main outcome measures Symptom profiles, details of taste and smell impact on personal and professional well-being. Effects on specific wine tasting attributes were also evaluated. Results Infected participants reported typical COVID-19 symptoms. The most frequent first noticed symptoms were sore throat (21.09%; 27/128), loss of taste or smell (19.53%; 25/128), fever (17.19%; 22/128) and cough (16.41%; 21/128). For those infected and sensory affected, the extent of taste and smell loss was most reported as severe in the majority of cases. The duration of taste and smell loss was resolved within 4 weeks for most participants. A vast proportion of participants reported an impact on their involvement in the wine profession, with the impact severity ranging from significant (20.31%; 26/128), somewhat (57.03%; 73/128), and not at all (22.66%; 29/128). Additionally, participants predominately reported having some impact on their overall quality of life, which was characterized as severe (7.14%; 9/126), moderate (37.30%; 47/126), mild (30.16%; 38/126), and none (25.40%; 32/126). Conclusion Wine professionals infected with COVID-19 and who experienced sensory alterations reported concerns about their professional and personal well-being with worries about a potential changing life narrative from losing vital sensory attributes. Policies to provide further resources, including therapeutics, for these professionals and others who suffer from sensory dysfunction are warranted.